A HOTAIR-associated super-enhancer orchestrates glioblastoma malignancy via MEST - Peng Li; Yang Yang; Chunpeng Luan; Wenbin Wang; Yuan Jiang; Zhenhao Zhao; Bo Wang; Yuting Zhao; Yunlong Bai; Man Liu; Zhongfang Zhao; Lei Zhang; et al. (Oncogenesis)
Abstract Glioblastoma (GBM) is one of the most malignant primary brain tumors, and factors governing its progression are not fully characterized. Recent research suggests that the long non-coding RNA (lncRNA) HOTAIR and super-enhancers (SEs) contribute significantly to GBM progression. Here, we performed TCGA data analysis revealing that high HOTAIR expression in GBM is associated with poor prognosis. Conversely, HOTAIR knock-down (KD) decreased proliferation, colony formation, and invasion of GBM cells. Furthermore, RNA-seq analysis identified DEGs in GBM cells related to cell growth and adhesion. Using an integrated approach, we also identify MEST as a HOTAIR-associated SE target gene. Intriguingly, MEST suppression in GBM cells phenocopied HOTAIR KD, as evidenced by reduced cell proliferation and invasion, whereas MEST overexpression counteracted effects of HOTAIR depletion. Moreover, 3 C technique-based PCR confirmed reduced interaction between HOTAIR-associated SEs and target genes after HOTAIR KD. This study reveals a novel regulatory mechanism governing GBM, offering promising directions for clinical interventions.